Targeting Cardiovascular Implant Infection: Multimodality and Molecular Imaging. (December 2017) - Sohns, Jan M.; Bavendiek, Udo; Ross, Tobias L.; Bengel, Frank M.
Abstract : Owing to their success in clinical practice, the prevalence of cardiovascular implants is continuously increasing. Implant infection is a relevant complication but remains a diagnostic challenge because echocardiography as a first-line test may be limited. Accordingly, a multimodality approach is increasingly used for diagnostic workup and supported by recent guidelines. As reviewed here, computed tomography and nuclear imaging provide incremental diagnostic value and may be combined in a single hybrid imaging session using positron emission tomography/computed tomography or single photon emission computed tomography/computed tomography. Molecular or cellular imaging helps to overcome the limitations of morphological imaging in implants. Larger-scale clinical studies, earlier application in the time course of diagnosis, monitoring of therapy success, technical advances, and novel radiopharmaceuticals will all contribute to sustained growth of advanced infection-targeted imaging in cardiovascular medicine. Abstract : Supplemental Digital Content is available in the text.